The Development and Validation of a Low-Cost Timing Gate Prototype as an Alternative to a Stopwatch in Agility Testing - Chaeroni, Ahmad; Huda, Asrul; Sombolon, Muhammad Eka Mardyansyah; Firdausi, Dzihan Khilmi Ayu; Pebriandani, Catur; Andristi, Ghina (Physical Education Theory and Methodology, 2025)
Background. Agility, defined as the physical attribute that enables individuals to swiftly alter their direction, is assessed through various tests, including body type assessments and sport-specific evaluations. It encompasses rapid alterations in the entire body, movements, and limb orientation. Agility plays a pivotal role in sports such as basketball, soccer, and racquetball, where prompt directional changes and precise body control are indispensable. Notably, the 505 test stands as the most reliable agility test, exhibiting a correlation with acceleration but not with speed. It monitors both speed and agility development. However, the prohibitive cost and accessibility challenges associated with the timing gate technology in Indonesia restrict its widespread application. Consequently, local sports practitioners continue to employ conventional stopwatches for their assessments. Objectives. The objective of this study was to develop a low-cost timing gate prototype that will be validated and approved by local users in Indonesia. The study evaluated the agreement between the 505 Agility Test measures, which utilize a stopwatch and a timing gate device that was constructed by the authors of the present study. Materials and Methods. The test protocol was administered to 40 fifth-semester students (9 females and 31 males) from the physical education study program in Indonesia. Results. The timing gate prototype was 0.19 seconds faster than the stopwatch measurement results (p <0.05). The prototype has also demonstrated excellent reliability. The Intraclass Correlation Coefficient (ICC) was found to be 0.920, with a 95% Confidence Interval (CI) of 0.848–0.958. Bland-Altman plots revealed a good level of agreement with the prototype. Conclusions. The findings indicate that the timing gate prototype is a potential replacement with a low cost for measuring timing results from conventional 505 agility tests using a stopwatch.